Numerical simulations of 2-D floating body driven by regular waves - 陈学彬 詹杰民 Qin CHEN (Journal of hydrodynamics. Series B, 2016)
An improved meshing method based on Fluent is used to update the computational meshes in solving the Navier-Stokes (N-S) equations for viscous and incompressible free surface flows with the volume of fluid (VOF) method. To maintain the mesh quality when updating meshes for a moving structure, the computational domain is separated into several parts and each part corresponds to a specific type of body motion. The numerical results of the interaction between the floating body and the regular waves agree well with the experimental data. A total of eight typical motion types are simulated separately to understand the correlation between the motion types and the wave transmission as well as the forces acting on the floating body. Numerical experiments show that the wave transmission increases in the case of sway and heave motions and decreases in the case of pitch motion as compared with the stationary case. It is also found that the sway motion reduces the horizontal wave force acting on the floating body, while the heave motion enhances the vertical wave force.